Hardening coating composition for MS resin
By using a combination of double-ended epoxy polyether polysiloxane copolymer and silane hydrolysate on the surface of the MS resin, combined with modified nano-scale inorganic oxides, the problem of poor adhesion of the hardening coating on the surface of the MS resin is solved, and a hardening coating with high adhesion, durability and high light transmittance is achieved.
Patent Information
- Application Number
- CN202411866476.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The polarity of MS resin is low, resulting in poor adhesion of hardening coatings, and is prone to failure during use, making it difficult to achieve high adhesion and comprehensive performance for a long time.
The double-ended epoxy polyether polysiloxane copolymer is used as the interface wetting agent, combining silane hydrolysate and nano-scale inorganic oxides, and the adhesion and hardness of the coating are improved by modifying the surface of the nano-scale inorganic oxides.
The adhesion and durability of the hardening coating to the surface of MS resin is significantly improved, the hardness and impact resistance of the coating are enhanced, while maintaining high light transmittance.
Smart Images

Figure BDA0005194481750000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hardened coatings and relates to a hardening coating composition for MS resin. Background Art
[0002] MS resin is a styrene (St)-methyl methacrylate (MMA) copolymer resin. In addition to the good processing fluidity and low hygroscopicity of polystyrene (PS), it also has the weather resistance and excellent optical properties of polymethyl methacrylate (PMMA). The refractive index of MS resin is 1.56, and its transparency is similar to that of PS. The light transmittance can reach 92%. It is a transparent, non-toxic thermoplastic.
[0003] MS resin has better flexibility than PMMA and lower hardness. It is more prone to surface scratches and abrasion during use, especially in the field of lenses, which require high surface scratch resistance. Improving the hardness of resin lenses is the main technical means to solve the problem of scratch resistance. For example, a layer of organic silicon-inorganic silicon hybrid hardening coating is applied on the surface of resin lenses, which has been widely used in polycarbonate (PC) lenses. However, compared with PC resin, MS resin has lower polarity. Although the resin surface is treated (such as ozone oxidation, corona treatment, etc.) before applying the hardening coating to increase its polarity, and a structure containing silanol or alkoxy silicon is used to improve the bonding strength, after a period of time, the resin surface will still gradually restore its low polarity characteristics, causing the hardening coating to gradually fail.
[0004] Document 1 discloses a hard coating composition comprising: (A) urethane (meth)acrylate, (B) multifunctional (meth)acrylate, (C) a polymer obtained by polymerizing a fluorine-containing (meth)acrylate, and (D) metal oxide fine particles. However, it does not disclose whether the adhesion of the hard coating layer is long-lasting.
[0005] Therefore, for MS resin, further research is needed on its hardening coating to achieve good adhesion durability of the hardening coating and better overall performance.
[0006] Document 1: CN104812853A. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a hardening coating composition for MS resin.
[0008] The technical solution of the present invention is as follows:
[0009] A hardening coating composition for MS resin, comprising, by weight, 100 parts of silane hydrolyzate, 0.3-10 parts of a double-terminal epoxy polyether polysiloxane copolymer, and 0-2 parts of an accelerator;
[0010] The silane hydrolyzate is obtained by hydrolyzing and condensing the silane compound represented by the following formula (1);
[0011] R 1 a R 2 b R 3 c Si(OR 4 ) 4-a-b-c (1)
[0012] Among them, R 1 is selected from C1-C24 alkyl or substituted C2-C36 alkyl, R 2 Selected from polyether segment structure, R 3 Selected from amino-substituted C2-C8 alkyl, R 4 Selected from H or C1-C4 alkyl, a≥0, b≥0, c≥0, <a+b+c<4。
[0013] Preferably, the values of a, b, and c satisfy: 0.05≤b / (a+b+c)≤0.2.
[0014] Preferably, the values of a, b, and c satisfy: 0.03≤c / (a+b+c)≤0.12.
[0015] Preferably, the double-terminal epoxy polyether polysiloxane copolymer is a block copolymer of polyether and polysiloxane.
[0016] More preferably, the molar ratio of the polyether to the polysiloxane is 1:2-2:1.
[0017] More preferably, the structure of the polyether is as shown in the following formula (2):
[0018] -(EO) x (PO) y -(2)
[0019] Wherein, EO represents a polyethylene oxide segment, PO represents a polypropylene oxide segment, x>0, y≥0, and x / (x+y)≥0.4.
[0020] Preferably, the accelerator is selected from imidazole compounds.
[0021] Preferably, the raw material components also contain 1-30 parts of nano-scale inorganic oxides.
[0022] More preferably, an organic group is chemically bonded to the surface of the nanoscale inorganic oxide, and the organic group contains an epoxy group or an amino group.
[0023] More preferably, the molar proportion of the epoxy group or the amino group in the organic group does not exceed 50%.
[0024] The beneficial effects of the present invention are:
[0025] (1) In view of the low polarity of MS resin, the present invention adopts a double-terminal epoxy polyether polysiloxane copolymer as an interfacial wetting agent to improve the wetting performance of the hardening coating composition on the surface of MS resin and promote the improvement of the bonding strength between the hardening coating and MS resin.
[0026] (2) The double-terminal epoxy polyether polysiloxane copolymer added in the present invention can also participate in the curing of the hardening coating composition, so that the double-terminal epoxy polyether polysiloxane copolymer can be stably and firmly distributed inside and on the interface of the hardening coating, playing a long-term wetting role, thereby improving the adhesion of the hardening coating.
[0027] Durability, and the double-terminal epoxy polyether polysiloxane copolymer can participate in the cross-linking reaction of the coating to avoid adverse effects on light transmittance.
[0028] (3) Nano-scale inorganic oxides may be added to the hardening coating composition of the present invention to further improve the hardness of the coating. By surface modification, the nano-scale inorganic oxides may participate in the cross-linking and curing of the hardening coating to improve the stability of the performance. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further illustrated and described below through specific implementation methods.
[0030] In order to improve the adhesion and adhesion durability of the hardening coating on the surface of MS resin, the present invention provides a hardening coating composition for MS resin, wherein the raw material components, by weight, include 100 parts of silane hydrolyzate, 0.3-10 parts of double-terminal epoxy polyether polysiloxane copolymer and 0-2 parts of accelerator;
[0031] The above-mentioned silane hydrolyzate is obtained by hydrolysis and condensation of the silane compound represented by the following formula (1);
[0032] R 1 a R 2 b R 3 c Si(OR 4 ) 4-a-b-c (1)
[0033] Among them, R 1 is selected from C1-C24 alkyl or substituted C2-C36 alkyl, R 2 Selected from polyether segment structures, R 3 Selected from amino-substituted C2-C8 alkyl, R 4Selected from H or C1-C4 alkyl, a≥0, b≥0, c≥0, <a+b+c<4。
[0034] In order to harden the MS resin, the present invention uses silane hydrolyzate as the main film-forming substance, which can be cross-linked to form an organic silicon-inorganic silicon hybrid hardening coating with high light transmittance and hardness. In order to solve the problem that the surface polarity of the MS resin is low and the coating is not easy to adhere, the present invention adds a double-terminal epoxy polyether polysiloxane copolymer to the silane hydrolyzate, and plays the following roles: (1) the polyether polysiloxane copolymer can effectively reduce the interfacial tension between the coating composition and the MS resin, and the coating composition has good wettability to the surface of the MS resin, promotes the formation of more reaction points between the silane hydrolyzate and the MS resin, and improves the bonding force and adhesion; (2) the terminal group of the polyether polysiloxane copolymer is an epoxy group, which can react with the amino group in the silane hydrolyzate and form a whole with the coating from a microscopic perspective. The polyether polysiloxane copolymer between the coating and the MS resin interface is also fixed and continuously and long-term plays a wetting role, so that the adhesion of the hardening coating to the MS resin is durable.
[0035] The weight percentage of the double-terminal epoxy polyether polysiloxane copolymer can further be 1-10 parts. For example, it can be any value among 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc., without special restrictions.
[0036] In a preferred embodiment of the present invention, the values of a, b, and c satisfy: 0.05≤b / (a+b+c)≤0.2, and the value of b / (a+b+c) represents R 2 The molar content of, for example, the value of b / (a+b+c) can be any value among 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, etc., without any particular limitation. More preferably, the values of a, b, and c satisfy: 0.08≤b / (a+b+c)≤0.15. In the present invention, R 2 The structure of is not particularly limited, for example, it can be -CH2CH2O(CH2CH2O) p (CH2CHCH3O) q R 4 , where p≥0, q≥0, p+q≥3, R 4 It can be H or C1-C8 alkyl. 2 The structure and molar content of the silane hydrolyzate can be adjusted to adjust the polarity of the silane hydrolyzate or its affinity with water, so that the silane hydrolyzate can be used in both oily systems and aqueous systems, or in a mixed system of water and polar solvents.
[0037] For the above silane hydrolyzate, R 3The role of is to fix the polyether polysiloxane copolymer in the coating by the reaction between the amino group and the epoxy group, and it mainly plays two roles: (1) providing a permanent wetting effect on the MS resin interface; (2) utilizing the flexible structure of the polyether polysiloxane to toughen the coating. In the preferred embodiment of the present invention, the values of a, b, and c satisfy: 0.03≤c / (a+b+c)≤0.12. The value of c / (a+b+c) represents R 3 The molar content of, for example, the value of c / (a+b+c) can be any value of 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, etc., without particular limitation. More preferably, the values of a, b, and c satisfy: 0.05≤c / (a+b+c)≤0.1. In the present invention, R 3 There is no particular limitation on the structure of the amino group, and the amino group may be a primary amino group or a secondary amino group. For example, R 3 The structure can be -(CH2)3NH2, -(CH2)3NHCH2CH2NH2, -(CH2)3NHCH3, -(CH2)3NHCH2CH3, etc.
[0038] In a preferred embodiment of the present invention, the double-terminal epoxy polyether polysiloxane copolymer is a block copolymer of polyether and polysiloxane. The block copolymer of polyether and polysiloxane has a good effect of reducing interfacial tension, can improve the wettability of the hardening coating composition to the MS resin, and promote the binding force between the silane hydrolyzate and the MS resin, and then utilize the reaction between the terminal epoxy group of the block copolymer and the amino group in the silane hydrolyzate, the block copolymer at the interface of the coating and the MS resin can stably stay and continue to play the role of wetting the MS resin interface, so that the adhesion of the hardening coating to the MS resin can be long-lasting. In the present invention, polysiloxane takes polydimethylsiloxane as an example, PE represents polyether, PDMS represents polydimethylsiloxane, and the structure of the block copolymer can be PE-b-PDMS, PE-b-PDMS-b-PE, PDMS-b-PE-b-PDMS, (PE-b-PDMS) nEtc. The preparation method of the block copolymer is well known to those skilled in the art, for example, it can be obtained by a silylation reaction between an epoxy-terminated allyl polyether and a double-terminated silane dimethylsiloxane, or by a silylation reaction between an epoxy-terminated allyl polyether and a single-terminated silane dimethylsiloxane, or by a ring-opening reaction between a double-terminated epoxy polyether and a single-terminated amino polydimethylsiloxane, or by a ring-opening reaction between a double-terminated epoxy polyether and a double-terminated amino polydimethylsiloxane, or by a ring-opening reaction between a double-terminated amino polyether and a double-terminated epoxy polydimethylsiloxane, or by a ring-opening reaction between a single-terminated amino polyether and a double-terminated epoxy polydimethylsiloxane, etc. In the present invention, there is no particular limitation on the structure of the epoxy group, for example, the structure of the epoxy-terminated allyl polyether can be (CH2CHO)CH2O-PE-CH2CH=CH2.
[0039] Further, in the present invention, the double-ended epoxy polyether polysiloxane copolymer can be composed of copolymers of different number average molecular weights, which has a further promoting effect on the flexibility and adhesion enhancement of the hard coating. For example, the double-ended epoxy polyether polysiloxane copolymer is composed of a copolymer with a lower number average molecular weight (the first copolymer) and a copolymer with a higher number average molecular weight (the second copolymer), the number average molecular weights of the first copolymer and the second copolymer can differ by more than 1000, or the number average molecular weight of the second copolymer can be 2 times or more of the number average molecular weight of the first copolymer, and the weight ratio of the first copolymer to the second copolymer can be 1:1-4:1.
[0040] In the present invention, the polysiloxane structure is not particularly limited, and the structure may be as shown in the following formula (3):
[0041] -(CH3)2SiO(SiOCH3CH3) m (SiOCH3R 5 ) n Si(CH3)2-, where R 5 It can be methyl, phenyl, propyl, trifluoropropyl, etc. The values of m and n can satisfy: m>0, n≥0, 5≤m+n≤100. 5 is phenyl and R 5 When the content is higher, the polysiloxane structure has a higher refractive index.
[0042] In a more preferred embodiment of the present invention, the molar ratio of polyether to polysiloxane is 1:2-2:1. For example, the molar ratio of polyether to polysiloxane can be 1:2, 1:1.5, 1:1, 1.5:1, 2:1, etc. Different molar ratios can be selected according to the specific different raw materials and / or reaction methods of polyether and polysiloxane. For example, the molar ratio of polyether to polysiloxane can be 1:1 by the hydrosilylation reaction of epoxy-terminated allyl polyether and single-terminated silane-hydrogen polydimethylsiloxane, and the molar ratio of polyether to polysiloxane can be 2:1 by the hydrosilylation reaction of epoxy-terminated allyl polyether and double-terminated silane-hydrogen dimethylsiloxane.
[0043] In a more preferred embodiment of the present invention, the structure of the polyether is shown in the following formula (2):
[0044] -(EO) x (PO) y -(2)
[0045] Wherein, EO represents a polyethylene oxide segment, PO represents a polypropylene oxide segment, x>0, y≥0, x / (x+y)≥0.4. The polyether can be composed of a polyethylene oxide segment and / or a polypropylene oxide segment. The polyethylene oxide segment has a higher polarity than the polypropylene oxide segment, which improves the surface activity and wetting properties of the double-ended epoxy polyether polysiloxane copolymer. The value of x / (x+y) represents the molar content of the polyethylene oxide segment in the polyether structure. For example, the value of x / (x+y) can be any value of 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, etc., without special restrictions. Further, the value of x+y can satisfy: 0.5≤x / (x+y)≤0.8.
[0046] In a preferred embodiment of the present invention, the accelerator is selected from imidazole compounds. Under the action of the accelerator, epoxy and amino groups can react faster and more completely, and the reaction temperature can also be lower, such as room temperature to 80° C. For example, the imidazole compound can be 2-methylimidazole, etc.
[0047] In a preferred embodiment of the present invention, the raw material components also contain 1-30 parts of nano-scale inorganic oxides. Adding nano-scale inorganic oxides to the hardening coating can further improve the hardness of the coating. The average particle size of the nano-scale inorganic oxide can be 1-80nm, which is lower than the wavelength of light, so it has little or no effect on the light transmittance of the coating. For example, the nano-scale inorganic oxide can be nano-SiO2, nano-TiO2, nano-ZrO2, nano-Al2O3, nano-ZnO, nano-CeO2, etc. The nano-scale inorganic oxide can be prepared by the corresponding sol, such as preparing nano-SiO2 by silica sol. For example, the number of nano-scale inorganic oxides can be any value of 1 part, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, etc., without special restrictions. More preferably, the number of nano-scale inorganic oxides can be 5-25 parts, or further, the number of parts is 5-20 parts. In the present invention, the nano-scale inorganic oxide can directly use the aqueous dispersion of the nano-scale inorganic oxide, such as nano-colloidal silicon Levasil R900, and when used, it needs to be converted according to the solid content of the aqueous dispersion.
[0048] In a more preferred embodiment of the present invention, the surface of the nano-scale inorganic oxide is chemically bonded to an organic group, and the organic group contains an epoxy group or an amino group. The surface of the nano-scale inorganic oxide is chemically bonded to an organic group, which can improve the compatibility and dispersibility in the coating composition, and avoid the influence on the light transmittance, hardness, etc. of the coating caused by uneven dispersion. The organic group contains an epoxy group or an amino group, which can participate in the cross-linking and curing reaction of the coating, so that the nano-scale inorganic oxide can be firmly dispersed in the coating through chemical bonding, and the binding force of the nano-scale inorganic oxide in the coating is enhanced, which can promote the improvement of the coating performance, such as impact resistance, hardness, etc.
[0049] In the present invention, chemically bonding organic groups on the surface of nanoscale inorganic oxides is well known to those skilled in the art and can be achieved in a variety of ways, such as using a silane coupling agent. For example, the silane coupling agent can be methyltrimethoxysilane, methyltriethoxysilane, dimethyldimethoxysilane, butyltrimethoxysilane, n-octyltrimethoxysilane, lauryltrimethoxysilane, 3-aminopropyltrimethoxysilane, β-aminoethyl-γ-aminopropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane, etc.
[0050] In a further preferred embodiment of the present invention, the molar proportion of epoxy or amino groups in the organic group does not exceed 50%. If the content of epoxy or amino groups in the organic group is high, it may cause the crosslinking density of the coating to be too high, which in turn reduces the adhesion and impact strength of the coating. For example, the molar proportion of epoxy or amino groups in the organic group can be any value of 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, etc., without special restrictions. The molar content of epoxy or amino groups in the organic group can be based on the molar ratio of the type of silane coupling agent added, such as methyl trimethoxy silane and 3-glycidyl ether oxypropyl trimethoxy silane in a molar ratio of 4:1, 3:2, 5:1, 2:1, 1:1, etc. for surface modification of nano-scale inorganic oxides.
[0051] There is no particular limitation on the preparation method of the hardening coating composition of the present invention, and the raw material components can be mixed and dispersed evenly. According to the needs of construction, the raw material components of the hardening coating composition can also contain solvents, such as water and / or organic solvents. The organic solvent can be: alcohol solvents, such as anhydrous ethanol, isopropanol, etc.; ether solvents, such as BCS, DPM, etc.; ketone solvents, such as methyl ethyl ketone, cyclohexanone, etc.; ester solvents, such as ethyl acetate, butyl acetate, etc. The hardening coating composition of the present invention can be applied to the surface of the MS resin by spraying, rolling, dipping, showering, etc., and the coating thickness can be 0.1μm-20μm.
[0052] The technical solution of the present invention is further described and illustrated according to various embodiments below. Unless otherwise specified, the parts described in the following embodiments are parts by weight.
[0053] The first copolymer 1-1 is obtained by a silylation reaction of epoxy-terminated allyl-terminated polyether (x=6.3, y=2.8 in the above formula (2)) and bi-terminal silyl dimethylsiloxane (m=20.7, n=0 in the above formula (3)) in a molar ratio of 2:1.
[0054] The first copolymer 1-2 is obtained by a 1:1 molar ratio of hydrosilylation reaction between an epoxy-terminated allyl-terminated polyether (x=7.5, y=6.1 in the above formula (2)) and a single-terminated silane dimethylsiloxane (m=15.8, n=0 in the above formula (3)).
[0055] The second copolymer 2-1 is obtained by a silylation reaction of epoxy-terminated allyl-terminated polyether (x=15.1, y=8.2 in the above formula (2)) and bi-terminal silyl dimethylsiloxane (m=37.4, n=0 in the above formula (3)) in a molar ratio of 2:1.
[0056] Example 1
[0057] The silane compound consists of butyltrimethoxysilane, polyethylene glycol (200) trimethoxysilyl propyl ether, methyltrimethoxysilane and 3-aminopropyltrimethoxysilane in a molar ratio of 40:10:43:7.
[0058] Preparation of silane hydrolyzate: Add 100 parts of silane compound into a reaction container, add 80 parts of anhydrous ethanol and 50 parts of purified water, stir and mix evenly, then add 3 parts of acetic acid, stir at room temperature for 3 hours, heat to 60-70°C, remove low-boiling substances under reduced pressure, and obtain silane hydrolyzate.
[0059] The raw material components of the hard coating composition are composed of 100 parts of the above-mentioned silane hydrolyzate, 5 parts of the above-mentioned first copolymer 1-1, 1 part of 2-methylimidazole, 30 parts of isopropanol and 50 parts of butyl acetate. The silane hydrolyzate, the first copolymer 1-1, isopropanol and butyl acetate are mixed and stirred to mix uniformly, and then 2-methylimidazole is added and stirred to mix uniformly to obtain a hard coating composition.
[0060] Example 2
[0061] The difference between this embodiment and embodiment 1 is that in embodiment 1, the first copolymer 1-1 is replaced by the second copolymer 2-1 of equal weight. The other steps remain unchanged.
[0062] Example 3
[0063] The difference between this embodiment and embodiment 1 is that in embodiment 1, the first copolymer 1-1 is replaced by the first copolymer 1-1 and the second copolymer 2-1 of equal weight in a weight ratio of 1:1. The other steps remain unchanged.
[0064] Example 4
[0065] The difference between this embodiment and embodiment 1 is that in embodiment 1, the first copolymer 1-1 is replaced by the first copolymer 1-2 and the second copolymer 2-1 of equal weight in a weight ratio of 3:1. The other steps remain unchanged.
[0066] Example 5
[0067] The difference between this embodiment and embodiment 1 is that in embodiment 1, the first copolymer 1-1 is adjusted from 5 parts to 1 part. The other steps remain unchanged.
[0068] Example 6
[0069] The difference between this embodiment and embodiment 1 is that in embodiment 1, the first copolymer 1-1 is adjusted from 5 parts to 10 parts. The other steps remain unchanged.
[0070] Comparative Example 1
[0071] The difference between this comparative example and Example 1 is that in Example 1, the first copolymer 1-1 is replaced by an equal weight of the wetting agent Tego 4100. The other steps remain unchanged.
[0072] Comparative Example 2
[0073] The difference between this comparative example and Example 1 is that in Example 1, the first copolymer 1-1 is replaced by 0.6 parts of the wetting agent Tego 4100. The other steps remain unchanged.
[0074] Comparative Example 3
[0075] The difference between this comparative example and Example 1 is that the first copolymer 1-1 is not added in Example 1. The other steps remain unchanged.
[0076] Comparative Example 4
[0077] The difference between this comparative example and Example 1 is that the first copolymer 1-1 in Example 1 is replaced by an equal weight of polyether-modified polysiloxane. The other steps remain unchanged.
[0078] The polyether-modified polysiloxane was prepared as follows: terminal allyl polyether CH2=CHCH2O(CH2CH2O) 6.5 (CH2CHCH3O) 2.2 The compound is obtained by a silylation reaction of CH3 and biterminal silyl hydrogen dimethyl siloxane (in the above formula (3), m=20.7, n=0) at a molar ratio of 2:1.
[0079] Example 7
[0080] The silane compound consists of ethyl orthosilicate, butyltrimethoxysilane, polyethylene glycol (400) trimethoxysilyl propyl ether, methyltrimethoxysilane and N-methyl-3-aminopropyltrimethoxysilane in a molar ratio of 15:18:12:40:15.
[0081] Preparation of silane hydrolyzate: Add 100 parts of silane compound into a reaction container, add 80 parts of anhydrous ethanol and 50 parts of purified water, stir and mix evenly, then add 3 parts of acetic acid, stir at room temperature for 4 hours, heat to 60-70°C to reduce the pressure and reduce the low boiling point to obtain silane hydrolyzate.
[0082] The raw material components of the hard coating composition are composed of 100 parts of the above-mentioned silane hydrolyzate, 6 parts of the above-mentioned first copolymer 1-2, 1 part of 2-methylimidazole, 50 parts of isopropanol and 50 parts of butyl acetate. The silane hydrolyzate, the first copolymer 1-2, 2-methylimidazole, isopropanol and butyl acetate are mixed and stirred uniformly to obtain the hard coating composition.
[0083] Example 8
[0084] The difference between this embodiment and embodiment 7 is that in embodiment 7, 30 parts of nano-SiO2 aqueous dispersion (nano-colloidal silicon Levasil R900) are added to the raw material components of the hardening coating composition. The other steps remain unchanged.
[0085] Example 9
[0086] The difference between this embodiment and embodiment 8 is that in embodiment 8, the weight of nano-SiO2 in the nano-SiO2 aqueous dispersion is replaced by 10.2 parts of amino-modified nano-SiO2. The other steps remain unchanged.
[0087] The preparation method of amino-modified nano-SiO2 is as follows: 50 parts of the nano-SiO2 aqueous dispersion in Example 8 are dispersed in 100 parts of anhydrous ethanol, 3 parts of a silane coupling agent composed of methyltrimethoxysilane and N-methyl-3-aminopropyltrimethoxysilane in a molar ratio of 4:1 are added, and stirred evenly. Then 10 parts of water are added, and stirred at room temperature for 3 hours. The solid is collected, and the solid is washed twice with anhydrous ethanol and dried in an oven at 60°C overnight to obtain amino-modified nano-SiO2.
[0088] Example 10
[0089] The difference between this embodiment and embodiment 9 is that in embodiment 9, the amino-modified nano-SiO2 is adjusted from 10.2 parts to 20 parts. The other steps remain unchanged.
[0090] Performance Testing
[0091] The hardening coating compositions of Examples 1-10 and Comparative Examples 1-4 were applied to a clean MS resin surface (the MS resin surface was not treated with corona etc.) by dipping, and directly transferred to an oven at 80° C. and heated for 3 h after dipping, and then taken out.
[0092] Adhesion: Tested according to the method of GB / T9286-1998.
[0093] Hardness: Tested in accordance with GB / T 6739-2006.
[0094] Impact strength: Tested in accordance with the method of GB / T22374-2018.6.3.10, the highest impact energy at which no cracks appear in the test coating.
[0095] Light transmittance: According to the method of GB / T2410-2008, the light transmittance in the visible light region was tested using a UV-visible spectrophotometer.
[0096] Thermal shock performance: 60℃×2h+-20℃×2h is one thermal shock cycle. Test 50 thermal shock cycles and then take out and place at room temperature for 24 hours before testing the adhesion of the coating.
[0097] Salt spray performance test: 5% sodium chloride, neutral saline, 37°C, test for 168 hours, rinse with clean water, wipe dry, and then place at room temperature for 24 hours before testing the adhesion of the coating.
[0098] The results are shown in Table 1 below.
[0099] Table 1
[0100]
[0101] It can be seen from the data results in Table 1 that the hardening coating composition of the present invention is used for the hardening coating of MS resin, and the coating has good adhesion, high light transmittance, and good impact resistance. After the hot and cold shock test and the salt spray test, it still has good adhesion.
[0102] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the content of the specification should still be within the scope of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.
Claims
1. A hardening coating composition for MS resin, characterized in that: The raw material components include, by weight, 100 parts of silane hydrolyzate, 0.3-10 parts of double-terminal epoxy polyether polysiloxane copolymer and 0-2 parts of accelerator; The silane hydrolyzate is obtained by hydrolyzing and condensing the silane compound represented by the following formula (1); R 1 a R 2 b R 3 c Si(OR 4 ) 4-a-b-c (1) Among them, R 1 is selected from C1-C24 alkyl or substituted C2-C36 alkyl, R 2 Selected from polyether segment structures, R 3 Selected from amino-substituted C2-C8 alkyl, R 4 Selected from H or C1-C4 alkyl, a≥0, b≥0, c≥0, <a+b+c<4。 2. The hardening coating composition for MS resin according to claim 1, characterized in that: The values of a, b, and c satisfy: 0.05≤b / (a+b+c)≤0.
2.
3. The hardening coating composition for MS resin according to claim 1, characterized in that: The values of a, b, and c satisfy: 0.03≤c / (a+b+c)≤0.
12.
4. The hardening coating composition for MS resin according to claim 1, characterized in that: The double-terminal epoxy polyether polysiloxane copolymer is a block copolymer of polyether and polysiloxane.
5. The hardening coating composition for MS resin according to claim 4, characterized in that: The molar ratio of the polyether to the polysiloxane is 1:2-2:
1.
6. The hardening coating composition for MS resin according to claim 4, characterized in that: The structure of the polyether is shown in the following formula (2): -(IS) x (PO) y -(2) Wherein, EO represents a polyethylene oxide segment, PO represents a polypropylene oxide segment, x>0, y≥0, and x / (x+y)≥0.
4.
7. The hardening coating composition for MS resin according to claim 1, characterized in that: The accelerator is selected from imidazole compounds.
8. The hardening coating composition for MS resin according to claim 1, characterized in that: The raw material components also contain 1-30 parts of nano-scale inorganic oxides.
9. The hardening coating composition for MS resin according to claim 8, characterized in that: The surface of the nanometer-scale inorganic oxide is chemically bonded with an organic group, and the organic group contains an epoxy group or an amino group.
10. The hardening coating composition for MS resin according to claim 9, characterized in that: The molar proportion of the epoxy group or the amino group in the organic group does not exceed 50%.
Citation Information
Patent Citations
Composition for hardcoat and molded article with hardcoat layer
CN104812853A
Non-ionic anion polysiloxane surfactant and preparation method thereof
CN101468301A
Preparation method and application of polyether-modified epoxy polysiloxane resin
CN102604117A
Triblock reactive compatibilizer and preparation method thereof
CN107057067A
Room temperature curing organic silicon transparent hard coating material and preparation method thereof
CN112876987A